Noninvasive Ventilation Initiation in Clinical Practice: A Six-Year Prospective, Observational Study - Chris Harris; Refik Saskin; Karen EA Burns (Canadian Respiratory Journal)
BACKGROUND: Despite evidence supporting the role of noninvasive ventilation (NIV) in diverse populations, few publications describe how NIV is used in clinical practice.